Personalized character of transgender medicine as a barrier to development of evidence-based clinical practice guidelines on gender incongruence - Ya. Kirey-Sitnikova (Медицинский вестник Юга России, 2022)
Gender transition medical procedures are effective in alleviating gender disphoria. However, their mechanisms of action are not yet fully understood. Hormone-replacement therapy (HRT) and surgeries modify sex characteristics. According to the biomedical model, perception of one's own sex characteristics is the primary contributor to gender dysphoria. Perception of the person in the wrong gender by others and/or their negative reaction is another (and less explored) mechanism leading to gender dysphoria. In order to conduct high-quality epidemiological studies, it is vital to take into consideration and measure intermediate outcomes, such as the degree of feminization/masculinization and the person's perceived gender. Sex characteristics are measurable, so it is possible to develop a feminization/masculinization scale. However, the task is complicated by the fact that various sex characteristics contribute unequally to the person's perceived gender, for which reason they should enter the scale with different coefficients. While such coefficients might be derived from controlled experiments, gender attibution in the real world depends on innumerable social factors. Reaction by others on the person's perceived gender is an additional factor affecting social gender dysphoria. Determining biological factors affecting the effectiveness of HRT in feminization and masculinization is a separate problem.